A feasible, acceptable and effective way to teach health care workers in low- and middle-income countries a method to manage acutely ill obstetric women. Issue 1 (January 2015) - McCarthy, Rose; Byrne-Davis, Lucie; Hart, Jo; Yuill, Gordon; Slattery, Helen; Jackson, Matthew; Byrne, Gerard J.
Abstract Maternal mortality is unacceptably high in Sub Saharan Africa, which accounts for 56% of all maternal deaths (WHO, 2012). Most maternal deaths are avoidable but with prompt recognition and timely intervention it is not inevitable that acute or critical maternal illness deteriorates to fatality (Firth and Ttendo, 2012). This paper discusses a project to provide multidisciplinary training in Maternal-Acute Illness Management (M-AIM) in a low resource setting in order to actively address the third delay to women accessing emergency obstetric care: prompt receipt of effective care on reaching a medical facility.